Guest editor's introduction to the Special Issue on Source Code Analysis and Manipulation (SCAM 2015). Issue 12 (14th December 2017) - Khomh, Foutse; Lo, David; Godfrey, Michael W.
Abstract: We are happy to introduce you to this special issue that presents selected papers from the 15th IEEE International Working Conference on Source Code Analysis and Manipulation (SCAM 2015). SCAM is a leading conference that brings together researchers and practitioners working on theory, techniques, and applications that concern analysis and/or manipulation of the source code of computer systems. While much attention in the wider software engineering community is properly directed towards other aspects of systems development and evolution, such as specification, design, and requirements engineering, it is the source code that contains the only precise description of the behavior of the system. The analysis and manipulation of source code thus remains a pressing concern. SCAM 2015 was held on September 27 to 28, 2015, in Bremen, Germany, together with 31st International Conference on Software Maintenance and Evolution (ICSME).